KRAS mutation status is associated with distinct clinical and molecular features in Malaysian stage IV colorectal patients - Amir, Azuwairie; Elagili, Faisal; Sainal, Mohd. Yusof; Md Nor, Azmi; Talib, Norlelawati A.; Aidid, Edre Mohammad (Wiley, 2022)
Aim: The purpose of this study was to estimate the prevalence of KRAS mutations in stage IV colorectal cancer in Malaysians and to investigate the associations of KRAS mutations with clinicopathological characteristics Method: All patients with stage IV colorectal cancer who underwent resection of the primary tumour between January 2017 and December 2021 were included in the single-center retrospective study. KRAS mutation status was determined. A multiple logistic regression model was used to analyse patient characteristics and tumour location Results: 41 patients (51% of whom were men) with an average age of 63 ± 13 years. The most common tumours were left-sided colon cancers (50%). The most common histological subtype was adenocarcinoma (95%). Thirty-two patients (78%) had LN metastasis. Twenty-nine patients (71%) had single-organ metastasis. The lung was the most common metastatic site (66%). KRAS mutation was found in 19 ( 46% ) of patients (63% in codon 12, 15% in codon 13, 15% in codon 61, and 7% in codon 117). KRAS mutation was found to be associated with rectal cancer in multivariable logistic regression analyses (odds ratio [OR] 6.8; confidence interval [CI] 1.41 to 33.2; p = 0.017). Conclusion: In t his study, K RAS mutations were found in 46% of patients with stage IV colorectal cancer. However, according to literature, the right-sided colon has a higher prevalence of mutated KRAS. In our study, the rectum was associated with a high KRAS mutation.